A revision of clusia l. section cochlanthera (choisy) engler (1977)
At an earlier time I published (Maguire, 1958) a review of the Section Cochlanthera of the genus Clusia L., admitting there five species. Now, after further field work in Colombia, I present an updated revision of the section with the addition of two new species, bringing the total to seven.